2015
DOI: 10.4209/aaqr.2014.10.0261
|View full text |Cite
|
Sign up to set email alerts
|

On-Road Emission Characteristics of Carbonyl Compounds for Heavy-Duty Diesel Trucks

Abstract: To study the emission characteristics of carbonyl compounds for in-use diesel vehicles on real roads, nine in-use heavyduty diesel trucks (HDDTs) representing different emission standards from China 0 to China 3 were tested on roads in Xiamen using an on-board carbonyl compound sampling system with a 2,4-DNPH cartridge. High-performance liquid chromatography (HPLC) was used to quantify the carbonyl compound emission factors. In total, 10 carbonyl compounds were detected for all the tested vehicles in this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The SEMTECH-DS is an important part of the PEMS, as explained in detail in our previous studies (Yao et al, 2011;Shen et al, 2014;Yao et al, 2015). The SEMTECH-DS can test the speed, latitude, longitude, elevation, air temperature, air humidity, exhaust temperature, and concentrations of CO, CO 2 , HC, and NO x in the exhaust.…”
Section: Data Synchronizationmentioning
confidence: 99%
“…The SEMTECH-DS is an important part of the PEMS, as explained in detail in our previous studies (Yao et al, 2011;Shen et al, 2014;Yao et al, 2015). The SEMTECH-DS can test the speed, latitude, longitude, elevation, air temperature, air humidity, exhaust temperature, and concentrations of CO, CO 2 , HC, and NO x in the exhaust.…”
Section: Data Synchronizationmentioning
confidence: 99%
“…Several techniques to reduce diesel engine emissions have been put forward including improving the mechanical design of the engine, but the diesel engine has been developed over century and the technology has matured. Other techniques include altering the characteristics of the diesel fuels by lowering the lower sulfur content to decrease SO x and adding additives such as alcohols, water containing acetone and dimethyl ethers Tsai et al, 2015a, b;Yao et al, 2015). Alternative fuels such as biodiesel and biodiesel-diesel blends have as also been considered (Chang et al, 2014a, b;Popovicheva et al, 2013;Mwangi et al, 2015b, c).…”
Section: Introductionmentioning
confidence: 99%
“…They have been used commonly in buses, heavy-duty trucks and generators. However, the emissions of particulate matter (PM) (Yao et al, 2015), nitrogen oxides (NO x ), sulfur dioxide (SO x ), unregulated pollutants such as polycyclic aromatic hydrocarbons (PAHs) (Cheruiyot et al, 2015), carbonyls (Yao et al, 2015) and halogenated persistent organic pollutants (POPs) from diesel engines are a major concern (Mwangi et al, 2015a;Cheruiyot et al, 2016), since they are are toxic to the human health (Popovicheva et al, 2013). Several techniques to reduce diesel engine emissions have been put forward including improving the mechanical design of the engine, but the diesel engine has been developed over century and the technology has matured.…”
Section: Introductionmentioning
confidence: 99%
“…Using PEMS to study real-world emission is thought to be a reliable, accurate and low-cost method (Kousoulidou et al, 2013). It has been frequently used in on-road vehicle emission studies (Huang et al, 2013;May et al, 2014;Vlachos et al, 2014;Yao et al, 2015) and has also been introduced to testing the emission of construction equipment. Frey et al (2008) tested several vehicles fueled with petroleum diesel and biodiesel, and proposed operating mode based method; Frey et al (2010) reported an on-board study of 39 pieces of construction equipment; Adolhasani et al (2012) provided a case study for 3 excavators; Fu et al (2012) firstly provided the onboard emission test result for non-road machinery in China.…”
Section: Introductionmentioning
confidence: 99%